The Impact of Covid-19 on Textile and Fashion Industries: The Economic Perspective - Febristi Arania; Irley Maura Putri; Muchammad Saifuddin (Politeknik Negeri Bandung, 2022)
The COVID-19 pandemic has not only had an impact on the health sector but also on the economy. The textile and fashion industry sector are once. Before the pandemic, the textile and fashion industry produced various kinds of fashion needs involving all its employees. Even in Indonesia, the textile and fashion industry is one of the most significant contributors to state revenue. However, during the pandemic, the textile and fashion industry sector decreased the amount of production. This article aims to determine the impact of Covid-19 on the textile and fashion industry from an economic perspective. This research is conceptual research by reviewing several related journals. Several journals found are then classified in several fields; the classifications that often appear are Marketing and Supply Chain. This article concludes that companies or organizations must dare to make changes and innovate the strategies they use quickly. It hoped that entrepreneurs could rise from economic adversity and adapt to current habits and environment.